Evaluation of In Vitro Capacitation of Buffalo Frozen/Thawed Sperm by Different Techniques - Elkhawagah, A. R.; Longobardi, V.; Gasparrini, B.; Sosa, G. A.; Bifulco, G.; Abouelroos, M.E. A.; el-ghafar, A.E. Abd; Camapnile, G. (Journal of Buffalo Science, 2014)
This study aimed to determine the most reliable method to evaluate capacitation of buffalo frozen/thawed sperm. Frozen/thawed sperm cells were incubated in Tyrode albumin lactate pyruvate medium (TALP) in absence of capacitating agents (control) and in presence of 10 µg/ml heparin for 2 and 4 h. Capacitation was assessed by Trypan blue/Giemsa after lysophosphatidylcholine (LPC) exposure, chlortetracycline (CTC) fluorescence assay and immune-localization of tyrosine phosphorylated protein. Furthermore, we evaluated the effect of heparin on penetration, cleavage rates and kinetics of embryo development after heterologous IVF. The percentage of LPC-induced acrosome reacted (AR)-sperm increased (P<0.05) with heparin compared to the control after 2 h (28.2 vs 24.4%, respectively) and 4 h (35.1 vs 32.0 %, respectively). No differences in CTC pattern B (capacitated sperm) were found between groups and incubation times (on average 63%). On the contrary, heparin decreased (P<0.01) the percentage of tyrosine phosphorylation pattern A after 2 and 4 h (34.3 and 35.3%, respectively) compared to the control (54.5 and 51.8%, respectively) and increased (P<0.01) that of pattern EA after 2 and 4 h (59.2 and 54.2 %, respectively) compared to the control group (44.7 and 45.2 %, respectively). Both cleavage and penetration rates, as well as the percentage of fast developing embryos, were higher (P<0.01) in the heparin-treated group (77.2, 80.4 and 74.0 %, respectively) compared to the control (56.6, 58.0 and 55.2 %, respectively). In conclusion, Trypan blue/Giemsa staining to evaluate LPC-induced AR and tyrosine protein phosphorylation assay can be successfully used to evaluate capacitation of buffalo frozen/thawed semen.